Difference between revisions of "P. 186, line 6"

From Bill Goodwine's Wiki
Jump to navigationJump to search
(Created page with "The equation should be <math>a_{n+1} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.")
 
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
 
The equation should be
 
The equation should be
  
<math>a_{n+1} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.
+
<math>a_{n+2} = -\frac{(\lambda - n)(\lambda + n + 1)}{(n+1)(n+2)}a_n</math>.
 +
 
 +
[[Engineering Differential Equations: Theory and Applications, Springer 2010#Errata|Return to errata.]]

Latest revision as of 16:09, 2 November 2011

The equation should be

.

Return to errata.